Production and Characterization of AlNiOZnOp-SiAl Composite Photodiodes for Solar Energy Tracking Systems - Gurgenc, Ezgi; Dikici, Aydın; Aslan, Fehmi (My University, 2022)
In present study, NiO:ZnO thin films in molar ratios of 1:0, 0:1, 3:1, 1:1 and 1:3 were formed on p-Si layers with aluminum (Al) bottom contact. Dynamic sol-gel spin coating method was used as coating method. Al top contacts were deposited on thin films and Al/NiO:ZnO/p-Si/Al photodiodes were fabricated. The structural and morphological properties of the photodiodes were determined by X-ray diffraction (XRD), emission scanning electron microscopy (FE-SEM), and energy dispersive X-ray spectroscopy (EDX). The photoresponse and electrical properties of the produced photodiodes were investigated by current–voltage (I–V) and capacitance-voltage (C-V) measurements. Al/NiO:ZnO/p-Si/Al photodiodes were successfully produced. It was determined that the thin films formed were composed of nanostructures. All photodiodes were found to be sensitive to light. It was seen that the photosensitivity of composite photodiodes was higher than the pure photodiodes and photosensitivity decreased as the ZnO ratio increased. It was determined that the most sensitive photodiode to light was the composite photodiode with a NiO:ZnO ratio of 3:1, and the highest photosensitivity was measured as 3.12 x 103 at 100 mW/cm2 light intensity in this photodiode. In all photodiodes, the capacitance values decreased as the frequency increased. The results show that by changing the NiO:ZnO ratio, the photoresponse and electrical parameters of the photodiodes can be controlled and the produced photodiodes can be used as a photosensor in solar tracking systems and optoelectronic applications.
Keywords: Composite photodiode; Sol-gel; Solar irradiation; Semiconductor metal oxide; Nanomaterial